Management of congenital choanal atresia: A pedodontist's role - Fathima Niloofar; Kumaran Parvathy; Balagopal R Varma; Xavier Arun Mamachan (Wolters Kluwer Medknow Publications, 2015)
Choanal atresia is a rare cryptic congenital anomaly with developmental failure of the nasal cavity to communicate with the nasophaynx, resulting in a significant physiological and anatomical alteration of the dento-facial complex. It is considered as a life-threatening or lethal congenital malformation in an obligatory nasal breathing neonate. Elective transnasal endoscopic repair is the most preferred and minimally invasive procedure to correct this anomaly. This case report describes the multi-disciplinary team approach that included pedodontists to manage the case of a 6-month-old infant with choanal atresia suffering from breathlessness, feeding difficulty, and disturbed sleep.